Feasibility of cantang grouper (Epinephelus fuscoguttatus x lanceolatus) hatchery in Klatakan Village, Kendit District, Situbondo Regency - Affandi, Rangga Idris; Setyono, Bagus Dwi Hari (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2024)
Cantang grouper has a very promising market for aquaculture industry. Situbondo Regency is one of the grouper seed producers with quite a large number of cultivators. One of them is in the Klatakan Village, Kendit District. The cantang grouper hatchery business cannot be separated from the economic aspect of the financial feasibility of the business. The aim of the research is to analyze the financial feasibility of the cantang grouper hatchery business in Klatakan Village, Kendit District, Situbondo Regency. This research was carried out in July-August 2019 in Klatakan Village, Kendit District, Situbondo Regency. Data collection was carried out through direct observation and the sampling technique used in this research was purposive sampling, that is, the researcher had certain considerations in taking samples or determining samples for certain purposes. The research results obtained were a profit of Rp. 166,133,600/year with an R/C Ratio of 1.9. Break Even Point (BEP) value in rupiah Rp. 122,808,219 and Break Even Point (BEP) in units of 34,217. Payback Period analysis obtained a value of 1.7 years or 1 year 8 months. It can be concluded that the cantang grouper hatchery business is profitable and feasible by looking at several of these indicators.